CRIMEAN CONGO HEMORRHAGIC FEVER: A LOOMING THREAT - Haroon, Muhammad Zeeshan; Farooq, Umer (Journal of Ayub Medical College Abbottabad, 2016)
Eid al Adha during CCHF transmission seasons poses a threat of exposing large population to this viral haemorrhagic fever. CCHF was first reported inCrimeain 1944. Oral ribavirin and general supportive therapy is the mainstay of treating CCHF case. Eid al Adha is a unique epidemiological event which shifts the risk of CCHF infection from high risk population to general population. During Eid, the prevention efforts must focus on reducing the risk of tick to human transmission, animal to human transmission and control of CCHF in animals and ticks